2005
DOI: 10.1158/0008-5472.can-05-0197
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histone H3 at Serine 10 Is Indispensable for Neoplastic Cell Transformation

Abstract: Very little is known about the role of histone H3 phosphorylation in malignant transformation and cancer development. Here, we examine the function of H3 phosphorylation in cell transformation in vivo. Introduction of small interfering RNA-H3 into JB6 cells resulted in decreased epidermal growth factor (EGF)-induced cell transformation. In contrast, wildtype histone H3 (H3 WT)-overexpressing cells markedly stimulated EGF-induced cell transformation, whereas the H3 mutant S10A cells suppressed transformation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 54 publications
(69 reference statements)
8
89
0
7
Order By: Relevance
“…Our own results are consistent with these previous studies because we showed that inhibition of Aurora A by CCT129202 resulted in the stabilization of p53 levels in tumor cells. Second, Aurora B has been shown to phosphorylate histone H3 at Ser 10 , and phosphorylation of histone H3 is associated with the induction of neoplastic transformation (41). Consistent with this, we showed that CCT129202 is a potent inhibitor of the phosphorylation of histone H3 in tumor cells.…”
Section: Discussionsupporting
confidence: 84%
“…Our own results are consistent with these previous studies because we showed that inhibition of Aurora A by CCT129202 resulted in the stabilization of p53 levels in tumor cells. Second, Aurora B has been shown to phosphorylate histone H3 at Ser 10 , and phosphorylation of histone H3 is associated with the induction of neoplastic transformation (41). Consistent with this, we showed that CCT129202 is a potent inhibitor of the phosphorylation of histone H3 in tumor cells.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, TPA and EGF are associated with a neoplastic cell transformation in JB6 Cl41 cells (46)(47)(48). Our results show that the overexpression of Pin1 induced a neoplastic cell transformation in JB6 Cl41 cells, and EGF enhanced the Pin1-induced cell transformation (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Recent data suggest that H3 histone phosphorylation is a major contributing factor for genome and chromosome instability and thus may play a role in cellular transformation and carcinogenesis. 60,61 Indeed, our results that demonstrated a substantial increase in histone H3S10 phosphorylation correspond to previous findings of overexpression of Aurora-A and chromosomal instability during breast carcinogenesis in ACI rats. 62 Furthermore, previous studies have demonstrated that genotoxic DNA-damaging agents can induce phosphorylation of H3S10 through the activation of the MAPK pathway.…”
Section: Resultssupporting
confidence: 91%